2018
DOI: 10.1039/c8nr04540b
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the signatures of nanoplasmon–exciton coupling on proton sensitive insulator–semiconductor devices for drug discovery applications

Abstract: Multimodal sensing methods have a great promise in biosensing applications as they can measure independently several properties that characterise the biomolecular interaction to be detected as well as providing inherent on-chip validation of the sensing signals. This work describes the mechanisms of a concept of insulator-semiconductor field-effect devices coupled with nanoplasmonic sensing as a promising technology, which can be used for a wide range of analytical sensing applications. The developed method in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, the good news is that most of these barriers are rapidly being addressed. Electrochemical and optical techniques on single platforms which can easily be translated into multiplexed panels are increasingly getting attention in both academia and industry, which might be able to serve the purpose of increased reliability and robustness required in the healthcare sensors, by instant authentication of the measured data. Disposable: The fact that the pandemic viral strains are highly infectious, for example, COVID-19 has a reproductive number higher than that established for SARS and H1N1, that is, between 1.5 and 2, the need for single-use sensors is crucial for avoiding contamination from the sensing systems. The most judicial pathway to develop a disposable sensor system is the modular approach. In this approach, electrode and readout modules can be separately designed where electrodes can be made cost-effective and disposable in nature.…”
Section: Biosensors For Early Detection and Prognosis Of Pandemic Vir...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the good news is that most of these barriers are rapidly being addressed. Electrochemical and optical techniques on single platforms which can easily be translated into multiplexed panels are increasingly getting attention in both academia and industry, which might be able to serve the purpose of increased reliability and robustness required in the healthcare sensors, by instant authentication of the measured data. Disposable: The fact that the pandemic viral strains are highly infectious, for example, COVID-19 has a reproductive number higher than that established for SARS and H1N1, that is, between 1.5 and 2, the need for single-use sensors is crucial for avoiding contamination from the sensing systems. The most judicial pathway to develop a disposable sensor system is the modular approach. In this approach, electrode and readout modules can be separately designed where electrodes can be made cost-effective and disposable in nature.…”
Section: Biosensors For Early Detection and Prognosis Of Pandemic Vir...mentioning
confidence: 99%
“…However, the good news is that most of these barriers are rapidly being addressed. Electrochemical and optical techniques on single platforms which can easily be translated into multiplexed panels are increasingly getting attention in both academia and industry, which might be able to serve the purpose of increased reliability and robustness required in the healthcare sensors, by instant authentication of the measured data.…”
Section: Biosensors For Early Detection and Prognosis Of Pandemic Vir...mentioning
confidence: 99%
“…For instance, Michelle et al showed that chemical interactions at the interface between the nanoparticle and the substrate contribute significantly to the differences observed in the experimental and theoretical LSPR sensitivities [18]. Very recently, Bhalla et al revealed that minute differences in the thickness and composition of silicon nitride led to large variations in LSPR-exciton coupling between gold (Au) nanostructures and insulator semiconductor nanojunctions [19]. Similarly, Knight et al showed spectral shifts and symmetry breaking of the LSPR by two adjacent dielectric substrates, inducing a plasmon hybridization [20,21].…”
Section: Introductionmentioning
confidence: 99%